Simulation Studies of Flood Along the Periyar River Basin, Central Kerala, India - Vijayan, Aswathy; SS, Praveen; Babu, Veena Suresh; S, Sajith Babu (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 8 No 2 (2021): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
Kerala experienced a large flooding during August 2018. One of the worst affected river basin in Kerala is the Periyar river basin causing many damages to the buildings, electricity circuits and agricultural fields. These vulnerabilities indicated the need for establishing a Flood Warning System (FWS). The main component of a FWS is the prediction of inundation and run-up along the banks of a river. Numerical modelling using models like HEC - RAS is an efficient tool, which is used to predict the flood generating events and future flood events for different permutations and combinations. In this investigation, a virgin mode of model computation is used to calculate the run-ups in which, only the rainfall is taken as the input. In this investigation, study area is the Periyar river basin. The input data such as topographic and bathymetric data were taken from different satellite sources. Extreme Rainfall Events (ERE) were taken from the Central Water Commission (CWC) report. Rainfall was mainly categorized in to four modes. They are normal, moderate, heavy and hypothetical rainfall. The modelling results showed a varying pattern. The prominent locations from Cheranalloor to Aluva show no run-up for normal rainfall. There is a significant change in the run-up for moderate rainfall which increases to 0.5 m. The moderate and hypothetical run-up values are found to be around 1.25 m and 2 m respectively. The inundation pattern for the hypothetical rainfall showed drastically increased values coming in the range of 1650 m for the eastern locations. From this investigation, it is clear that a normal and moderate rainfall will not cause significant run-up and inundation, whereas continuous mode of heavy rainfall events contributing to extreme rainfall events can cause a significant run-up along the coast. This investigation will help the ongoing research and development trajectory to establish a FWS in Kerala with specific reference to Kerala floods 2018. How to cite this article: Aswathy V, Praveen SS, Babu VS et al. Simulation Studies of Flood along the Periyar River Basin, Central Kerala, India. J Adv Res Geo Sci Rem Sens 2021; 8(2): 1-7.